Effect of concentration and relative position of wood and coal particles on the characteristics of the mixture ignition process; Fuel; Vol. 274 - Kuznetsov G. V. Geny Vladimirovich; Syrodoy S. V. Semen Vladimirovich; Kostoreva A. A. Anastasiya Andreevna; Kostoreva Zh. A. Zhanna Andreevna; Nigay N. A. Nataljya Andreevna (2020, 2020)
Title screen